Developmental Accretion of Docosahexaenoic Acid Is Independent of Fatty Acid Transporter Expression in Brain and Lung Tissues of C57BL/6 and Fat1 Mice. Issue 10 (10th June 2019) - Yakah, William; Singh, Pratibha; Perides, George; Brown, Joanne; Freedman, Steven D; Martin, Camilia R
ABSTRACT: Background: Developmental expression of fatty acid transporters and their role in polyunsaturated fatty acid concentrations in the postnatal period have not been evaluated. Objective: We hypothesized that transporter expression is developmentally regulated, tissue-specific, and that expression can modulate fatty acid accretion independently of diet. Methods: Brain and lung transporter expression were quantified in C57BL/6 wild-type (WT) and Fat1 mice. Pups were dam-fed until day 21. Dams were fed AIN-76A 10% corn oil to represent a typical North American/European diet. After weaning, mice were fed the same diet as dams. Gene expression of Fatp1, Fatp4, Fabp5, and Fat/cd36 was quantified by quantitative reverse transcriptase-polymerase chain reaction. Fatty acid concentrations were measured by GC–MS. Results: Brain docosahexaenoic acid (DHA) concentrations increased from day 3 to day 28 in both genotypes, with higher concentrations at days 3 and 14 in Fat1 than in WT mice [median (IQR)]: 10.7 (10.6–11.2) mol% compared with 6.6 (6.4–7.2) mol% and 12.5 (12.4–12.9) mol% compared with 8.9 (8.7–9.1) mol%, respectively; P < 0.05). During DHA accrual, transporter expression decreased. Fold changes in brain Fatp4, Fabp5, and Fat/cd36 were inversely correlated with fold changes in brain DHA concentrations in Fat1 relative to WT mice (ρ = −0.85, −0.75, and −0.78, respectively; P ≤ 0.001). Lung DHA concentrations were unchanged across the 3 time points for both genotypes. Despite unchanging DHA concentrations, there was increased expression of Fatp1 at days 14 and 28 (5-fold), Fatp4 at day 14 (2.3-fold), and Fabp5 at day 14 (3.8-fold) relative to day 3 in Fat1 mice. In WT mice, Fatp1 increased almost 5-fold at day 28 relative to day 3. There was no correlation between lung transporters and DHA concentrations in Fat1 relative to WT mice. Conclusions: Development of fatty acid transporter expression in C57BL/6 WT and Fat1 mice is genotype and tissue specific. Further, postnatal accretion of brain DHA appears independent of transporter status, with tissue concentrations representing dietary contributions.